SISTEM INFORMASI DAN PEMETAAN RUMAH SAKIT KOTA TANGERANG BERBASIS WEB - Agmal Anwar (CV. Multi Kreasi Media, 2024)
The information system at Tangerang City Hospital has some information such as Hospital Information, Doctor Information, Doctor Schedule Information, Room Information available at the Hospital, Hospital Facilities Information, and Hospital Event Information. The purpose of creating this health service information system is to help people who have trouble finding the specialist doctor they need and the location of the hospital we want to be able to get direct directions via Google Maps. because this system is already connected to the internet. System development with the objectives that have been described, using the prototype development method with the stages of gathering needs, building prototypes, evaluating prototypes, coding systems, testing systems, evaluating systems, and using systems. Designing a system, of course, requires tools using the Unified Modeling Language (UML) with use case diagrams, activity diagrams, sequence diagrams, class diagrams. The results obtained from the design and construction of this system provide information, Hospital Information, Doctor Information, Doctor Schedule Information, Room Information available at the Hospital, Hospital Facilities Information, and Hospital Event Information